ANALISIS PENGARUH KUALITAS PELAYANAN, EFEKTIVITAS PENGAWASAN, PEMAHAMAN KETENTUAN PERPAJAKAN, KONSULTASI, SOSIALISASI DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK BADAN DENGAN PROFESIONALISME ACCOUNT REPRESENTATIVE SEBAGAI VARIABEL MODERATING - YUNITA ERIYANTI PAKPAHAN (JURNAL ILMIAH MAKSITEK, 2018)
The objective of the research was to find out, analyze, and prove empirically service quality, taxation socialization, sanction, and taxpayers environment on corporate taxpayers compliance and account representative professionalism as moderating variable in KPP (Tax office) Madya Sumut 1. The population was 927 corporate taxpayers registered in the KPP Madya Medan. The samples were taken by using cluster random sampling technique. The data were gathered by distributing questionnaires, and only 91 respondents who returned them and analyzed by using multiple linear regression analysis and residual analysis for moderating variable. The result of the research showed that, service quality, taxation socialization, sanction, and taxpayers environment partially and simultaneously had the influence on corporate taxpayers’ compliance at KPP Madya Sumut 1. Account representative professionalism as moderating variable could strengthen the correlation of service quality, taxation socialization, sanction, and taxpayers environment with corporate taxpayers compliance at KPP Madya Sumut 1.